Examination of the Association between Insufficient Sleep and Cardiovascular Disease and Diabetes by Race/Ethnicity. (29th May 2011) - Vishnu, Abhishek; Shankar, Anoop; Kalidindi, Sita
Abstract : Background . We examined the association between insufficient rest/sleep and cardiovascular disease or diabetes mellitus separately among non-Hispanic whites, non-Hispanic blacks, Hispanic Americans, and other races in a contemporary sample of US adults. Methods . Multiethnic, nationally representative, cross-sectional survey (2008 BRFSS) participants who were >20 years of age (n = 369, 217; 50% women). Self-reported insufficient rest/sleep in the previous month was categorized into: zero, 1–13, 14–29, and all 30 days. Outcomes were: (1) any CVD, (2) coronary artery disease (CHD), (3) stroke, and (4) diabetes mellitus. Results. Insufficient rest/sleep was found to be positively associated with (1) any CVD, (2) CHD, and (3) stroke among all race-ethnicities. In contrast, insufficient rest/sleep was positively associated with diabetes mellitus in all race-ethnicities except non-Hispanic blacks. The odds ratio of diabetes association with insufficient rest/sleep for all 30 days was 1.37 (1.26–1.48) among non-Hispanic whites, 1.11 (0.90–1.36) among non-Hispanic blacks, 1.88 (1.46–2.42) among Hispanic Americans, and 1.48 (1.10–2.00) among other race/ethnicities. Conclusion . In a multiethnic sample of US adults, perceived insufficient rest/sleep was associated with CVD, among all race-ethnicities. However, the association between insufficient rest/sleep and diabetes mellitus was present among all race-ethnicities except non-Hispanic blacks.